Perkembangan Emosi dan Sosial Pada Anak Usia Dini - Novi Mulyani (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract Human development is a complex process, which can be divided into four major domains, namely the physical, intellectual (including cognitive and language), as well as emotional and social (including moral development). In this paper the author will learn about the social and emotional development in early childhood. Social-emotional development of children is the sensitivity to understand other people’s feelings when interacting in everyday life. Social-emotional development is true can not be separated from each other. When discussing the social development of children it must intersect with the emotional development of children. Keywords: developmental, social, emotional, child.